Development of a genome-editing CRISPR/Cas9 system in thermophilic fungal Myceliophthora species and its application to hyper-cellulase production strain engineering. Issue 1 (December 2017) - Liu, Qian; Gao, Ranran; Li, Jingen; Lin, Liangcai; Zhao, Junqi; Sun, Wenliang; Tian, Chaoguang
Abstract Background Over the past 3 years, the CRISPR/Cas9 system has revolutionized the field of genome engineering. However, its application has not yet been validated in thermophilic fungi.Myceliophthora thermophila, an important thermophilic biomass-degrading fungus, has attracted industrial interest for the production of efficient thermostable enzymes. Genetic manipulation ofMyceliophthora is crucial for metabolic engineering and to unravel the mechanism of lignocellulose deconstruction. The lack of a powerful, versatile genome-editing tool has impeded the broader exploitation ofM. thermophila in biotechnology. Results In this study, a CRISPR/Cas9 system for efficient multiplexed genome engineering was successfully developed in the thermophilic speciesM. thermophila andM. heterothallica . This CRISPR/Cas9 system could efficiently mutate the importedamdS gene in the genome via NHEJ-mediated events. As a proof of principle, the genes of the cellulase production pathway, includingcre -1, res -1, gh1 -1, andalp -1, were chosen as editing targets. Simultaneous multigene disruptions of up to four of these different loci were accomplished with neomycin selection marker integration via a single transformation using the CRISPR/Cas9 system. Using this genome-engineering tool, multiple strains exhibiting pronounced hyper-cellulase production were generated, in which the extracellular secreted protein and lignocellulase activities were significantly increased (up to 5- and 13-fold, respectively) compared with the parental strain. Conclusions A genome-wide engineering system for thermophilic fungi was established based on CRISPR/Cas9. Successful expansion of this system without modification toM. heterothallica indicates it has wide adaptability and flexibility for use in otherMyceliophthora species. This system could greatly accelerate strain engineering of thermophilic fungi for production of industrial enzymes, such as cellulases as shown in this study and possibly bio-based fuels and chemicals in the future.